1996
DOI: 10.1007/bf03163103
|View full text |Cite
|
Sign up to set email alerts
|

An EPR investigation of the phase transitions and cooperative ordering phenomena of pentaamminecopper(II) polyhedra in Cu(NH3)5X2 [X=BF4, CIO4; Br]

Abstract: Abstraer, The results of powder and single-crystal EPR studies on Cu(NH3)sX 2 compounds [X = BF4, CICI4; Br] gire evidence that phase transitions from a eubic c~-phase (g, = 2.12) with ma anti-K2PtCl 6 type structure to low-temperature ~-phases with reduced symmetry occur, which ate indur by orderhag proeesses of the vacaneies 3 of elongated [Cu0qH3)~l~] 2+ pseudo-oetahedra. The b'pe of order is crucially eontrolted by the nature of the anion, la the case of the BF4-and CIOg ~lts the large an[ons ate s'mueture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…The g-factor is equal to 2.123. The linewidth was not reported [5]. EPR results on [Cu(NH 3 ) 5 ](BF 4 ) 2 •0.1NH 3 , presented in this paper, give g = 2.130 and a linewidth of 31 G. For perchlorates [Cu(NH 3 ) 5 ](ClO 4 ) 2 •xNH 3 the EPR data are available for x = 0 [5], x ≈ 0.1 [6] and x = 0.2 [1].…”
Section: The Role Of 'Lattice Ammonia' Molecules In the Averaging Of ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The g-factor is equal to 2.123. The linewidth was not reported [5]. EPR results on [Cu(NH 3 ) 5 ](BF 4 ) 2 •0.1NH 3 , presented in this paper, give g = 2.130 and a linewidth of 31 G. For perchlorates [Cu(NH 3 ) 5 ](ClO 4 ) 2 •xNH 3 the EPR data are available for x = 0 [5], x ≈ 0.1 [6] and x = 0.2 [1].…”
Section: The Role Of 'Lattice Ammonia' Molecules In the Averaging Of ...mentioning
confidence: 99%
“…Equation ( 2) applied to the analysis of the g-factor change at T c in [Cu(NH 3 ) 5 ](ClO 4 ) 2 •0.2NH 3 (total number of ammonia molecules per Cu(II) ion n = 5.2) showed that the decrease in the volume at the phase transition shifts the equilibrium to the SQP configuration of the Cu(II) ion [4]. The analysis of EPR data of penta-ammino copper(II) perchlorate [Cu(NH 3 ) 5 ](ClO 4 ) 2 • xNH 3 [1,5,6] revealed that there is a significant influence of additional 'lattice ammonia' molecules (not forming [Cu(NH 3 ) 5 ] 2+ complex), hereafter denoted as x, where n = 5 + x, on the g-factor of the EPR line in the high temperature phase [6]. Below the phase transition temperature (T c = 142 K [1] and 153 K [7] for perchlorate and T c = 154 K [5] and 130 K [8] for fluoroborate) the EPR pattern substantially depends on the number of non-coordinated ammonia molecules.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations